Análise dos efeitos comportamentais e potencial tóxico de um inseticida à base de carbosulfan e bifentrina em Drosophila melanogaster - Navarro, Jullya Rozendo (Universidade Federal de São Carlos, 2025)
Insecticides are widely used in agricultural production, and their residues in soil, water, and agricultural products pose a risk to the entire ecosystem. One of the techniques used to study the toxic effects of these chemicals is biomonitoring. Drosophila melanogaster Meigen, 1830 (Diptera) is a genetically well-explored organism, with a rapid biological cycle, easy maintenance, and, after the complete sequencing of its genome, revealed about 75% genetic homology with humans, including brain structure and functioning. This study evaluated the behavioral effects and toxic potential of an insecticide based on carbosulfan and bifenthrin. The toxicity assays with the flies lasted 168 hours (7 days). The experimental design included five treatments and one control group (0; 0.126; 1.26; 12.6; 126 and 1260 μL/L) with three replicates each. The results showed an LC50 of 11.08 μL/L and a median effective concentration (EC50) for negative geotaxis of 10.21 μL/L. The lowest observed effect concentration (LOEC) for behavioral changes was 0.126 μL/L. The Spearman correlation analysis indicated a negative association between the insecticide concentration and the survival rate (ρ = -0.808; p < 0.001). No statistically significant differences were observed between sexes in the susceptibility to the insecticide. The results indicate that the commercial formulation presents synergistic effects, with neuromotor impairments detectable at sublethal concentrations lower than the lethal levels used in agriculture (6 mL/L for soybean crops). The present study concludes that the commercial product based on the active ingredients bifenthrin and carbosulfan presents significant environmental risks to non-target organisms, highlighting the importance of including regulatory assessment and risk protocols that incorporate behavioral parameters in non-target organisms.
Analysis of the behavioral effects and toxic potential of a carbosulfan and bifenthrin-based insecticide on Drosophila melanogaster
Keywords: Inseticida; Insecticide; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL; 6. Água Potável e Saneamento; 12. Consumo e Produção Responsáveis